(untitled) (Current Problems in Rail Vehicles, 2021)
Introduction of the Stadler Rail company, inclusion of the Stadler Prague engineering office within the Stadler Rail group and information about implemented projects in Central European countries. A more detailed presentation of individual implemented projects of new rolling stock, information on interesting facts or specific individual projects, which were completely or at least partially processed in Stadler Prague.